2021
DOI: 10.12973/eu-jer.10.2.813
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Online Project Collaborative Learning and Achievement Motivation on Problem-Solving Ability

Abstract: The aim of this study is to find out the influence of online project collaborative learning and achievement motivation on problem-solving ability in the area of citizenship. This study uses a quasi-experimental design. The total of study subjects is 71 students of higher education; consist of 36 students as the experimental group and 35 students as the control group. Data of problemsolving ability is obtained by using an essay test, while data of achievement motivation is obtained by using a questionnaire. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…This is clearly expressed in item 1 (M=63), 2 (M=60) and 3 (M=58),, which show that students have favorable attitudes towards the online experience as it helped them foster exchange of knowledge and information, facilitated problem-solving, and promoted their higher critical thinking skills. This is in line with a number of studies (Kalayci, 2014;Lee & Osman, 2021;Yunus et al, 2021). This is not surprising as they also highly agreed with items 12 (M= 4.47) and 23 (M= 4.42) and 6 (M= 4.33) where they clearly agreed that online collaborative writing enables them to spend more time checking spelling and punctuation.…”
Section: Research Question Two: What Is the Students' Attitude Toward...supporting
confidence: 88%
See 1 more Smart Citation
“…This is clearly expressed in item 1 (M=63), 2 (M=60) and 3 (M=58),, which show that students have favorable attitudes towards the online experience as it helped them foster exchange of knowledge and information, facilitated problem-solving, and promoted their higher critical thinking skills. This is in line with a number of studies (Kalayci, 2014;Lee & Osman, 2021;Yunus et al, 2021). This is not surprising as they also highly agreed with items 12 (M= 4.47) and 23 (M= 4.42) and 6 (M= 4.33) where they clearly agreed that online collaborative writing enables them to spend more time checking spelling and punctuation.…”
Section: Research Question Two: What Is the Students' Attitude Toward...supporting
confidence: 88%
“…In a quasi-experimental, Yunus et al (2021) examined the influence of online project collaborative learning and achievement motivation on problem-solving ability. The study sample Arab World English Journal www.awej.org ISSN: 2229-9327 305 consisted of 71 students of higher education divided equally into two experimental and control groups.…”
Section: Introductionmentioning
confidence: 99%
“…This stage also provides opportunities for students to expand the knowledge that has been obtained by challenging wider problems. Yunus et al [43] stated that the provision of additional teaching materials and their variations in online learning is closely related to students' achievement motivation and can improve students' problem-solving abilities.…”
Section: Product Eligibilitymentioning
confidence: 99%
“…It has also been proved that achievement motivation is relevant to problem-solving ability. In a quasi-experimental study (Yunus et al, 2021), researchers discussed the correlation between achievement motivation and the problem-solving ability of students in an online program. The results showed that the problem-solving ability was different between the students with high achievement motivation and those with low achievement motivation.…”
Section: Relations Between Variablesmentioning
confidence: 99%